Risk Mitigation Through Integration COSO-Enterprise Risk Management And ISO 31000 in Higher Education - Syahrullah, Yudi; Annai Nashida, Aulia; Prakoso, Indro; Two Nando, Fiky (International Journal of Educational Management and Innovation, 2025)
Background. Higher education institutions are given targets to meet key performance indicators (KPI) and to meet study program accreditation instruments. Several new requirements in study program accreditation make it difficult for universities to achieve their targets. Risk management can help organizations reduce risks that hinder them from achieving performance targets. This study aims to identify risks and provide risk assessments to produce mitigation proposals for the Department of Higher Education. Materials. The risk management framework used in this study is integration through ISO 31000 with COSO-ERM, where risk management is carried out comprehensively internally and externally. This research involved experts from a university in Central Java designing risk impact parameters, assessing risks, and designing risk mitigation. Results. The results of this study indicate that the residual risk assessment resulted in 8 low-category risks, 7 medium-category risks, 7 high-category risks, and 1 extreme-category risk. The risks given control (residual) increased by seven risks, and mitigation proposals must be provided. Then, 9 risks exceeded the tolerance limits set by top management, so recommendations for risk mitigation had to be proposed to achieve the Institution's performance targets. Conclusion. Risk Management can be applied to universities to achieve the set goals or targets. The integration of COSO-ERM and ISO 31000 methods can complement the stages in risk management, especially in risk identification, risk analysis, and setting risk tolerance limits in risk assessment, so that the risk mitigation designed is in line with the targets to be achieved by the university.